Review of Handbook of Development Economics - Fishlow, Albert (Journal of Economic Literature, 1991)
ECONOMIC DEVELOPMENT is a field in search of itself. Within the last few years several surveys have appeared, ranging from article length to the definitive two volume Handbook of Economic Development with its 33 chapters and 1700 pages., 2 Even the World Bank's 1991 World Developmnent Report is devoted for the first time to a review of the fundamentals of the subject, rather than its customary analysis of specific problems like human resources, agriculture, industry, etc. This industry of self-reflection thrives from a conjunction of two circumstances. One is the disturbing reality of the lost decade of the 1980s which saw negative per capita economic growth for the countries of Africa and Latin America, even while positive results were being realized in most parts of Asia. for the first time in the postwar period, the presumption of continual